Pollution Enteroparasites in cabbage marketed in Lara, Yaracuy and Portuguesa states (Revista Venezolana de Salud Pública, 2018)
Intestinal parasites are a public health problem and cabbage is a possible vehicle. In order to determine the enteroparasites contamination of cabbages marketed in major cities of Lara, Yaracuy and Portuguesa States, during the period from July to November 2012, we conducted a cross-sectional study with a convenience sample accidental, in 120 cabbages using the Alvarez technique modified by Traviezo et al. It was found that 10.83% had presence of intestinal parasites. The frequency in Yaracuy State was 17,50%, 12,50% Lara and Portuguesa 2,50%. The species found were Blastocystis hominis, Chilomastix mesnili, Entamoeba histolytica, Balantidium coli, Endolimax nana and Strongyloides sp., Dipylidium caninum, Blastocystis hominis being the most common pathogen enteroparasites with 38,46%. Depending on the source of the contaminated samples were from 12,50% MERCABAR, whose exact origin is unknown, followed by those who came from Mérida with 11.10%. Depending on the type of establishment, it was found that 16,70% of the samples were contaminated acquired by enteroparasites markets, 11,10% supermarket and 7,60% for supplies. In relation to the hygiene of the establishment, it was observed that were contaminated by enteric 13,51% of the samples acquired local poor sanitation, 10% in the optimum, 7,14% in good and 4,54% in regular. Conclude that the percentage of enteroparasites contamination of cabbages in the region was low, however, constitutes a risk factor for the development of food-borne parasitic diseases.
Keywords: Contamination; cabbage; enteroparasites; NaWuarao